دور المدرسة في الحد من الانفلات الاجتماعي تحقيقا للأمن المجتمعي - بن ققة، سعاد; شريف، حورية علي (مؤسسة كنوز الحكمة للنشر والتوزيع, 2023)
تهدف هذه الورقة البحثية إلى تسليط الضوء على قضية هامة تطرح وبشكل كبير على المستوى المجتمعي وفي جميع الميادين، الأكاديمية والمدنية، والسياسية والثقافية وغيرها من الميادين، لمدى أهميتها، في حياة الفرد واستقرار المجتمع وتنميته، قضية الأمن المجتمعي، والذي إذا اختل ينتج عنه الانفلات الاجتماعي، الذي أخذ أبعاد عدة، وزادت حدته نتيجة لحالة الأنوميا التي يعيشها المجتمع الجزائري بسبب اهتزاز منظومة القيم، وانتشار القيم النفعية والاختراق الثقافي، الناتج عن العولمة، وما خلفته الوسائط التكنولوجية الحديثة من تفتح على الثقافات الأخرى، التي تختلف عن خصوصية المجتمع الجزائري وهويته، وباتت تهدده امنه الاجتماعي، ما يستدعى تكاثف مختلف مؤسسات المجتمع لتصدى لهذا الوضع، وعلى رأسها مؤسسات التنشئة الاجتماعية، والتي من أهمها المدرسة، التي سنحاول إبراز دورها في الحد من هذا الانفلات الاجتماعي من خلال غرس وترسيخ قيم الانتماء الاجتماعي لدى الفرد، وكذا تعزيز علاقته بالدولة، فضلا المشاركة في حل الأزمة اللغوية في الجزائر إلى جانب قضايا هامة أخرى، لها علاقة بتحقيق الأمن الاجتماعي في الجزائر منطلقين من التساؤل التالي: إلى أي مدى تساهم المدرسة في الحد من الانفلات الاجتماعي تحقيقا للأمن المجتمعي؟. This research Paper amis to shed light on an important issue that arises largely at the societal level, and in all fields, Academic, civil, political, cultural, and other Fields, due to its importance, in the life of the individual and the stability and development of society, the issue of societal security, which, if disturbed, results. Social chaos has taken on several dimensions, and its severity has increased as a result of the state of anemia that Algerian society is experiencing due to the vibration of the value system, the spread of utilitarian values and cultural penetration, resulting from globalization, and the openness left by modern technological media to other cultures, which differ from the specificity of society. The Algerian and his identity, and his social security has become threatened, which requires the intensification of various institutions of society to confront this situation, most notably the institutions of socialization, the most important of which is the school, whose role we will try to highlight in reducing this social chaos by instilling and consolidating the values of social belonging in the individual, as well as. Strengthening his relationship with the state, as well as participating in resolving the linguistic crisis in Algeria, along with other important issues related to achieving social security in Algeria, starting from the following question. To what extent does the school contribute to reducing social chaos in order to achieve community security.
Keywords: المؤسسات التربوية -- الهوية اللغوية -- السلوكيات الاجتماعية -- القيم الأخلاقية -- المجتمع الجزائري